Innovation in Companies operating in the Foodstuffs Sector of Colombia. An analysis from the perspective of open innovation - Agredo Diaz, Martha Lucia; Silva Castellanos, Tulio Ferney (Cuadernos de Administración, 2018)
his study explores the characteristics of open innovation within the foodstuffs industry in Colombia, contrasting the importance recognized by its actors of this way of generating innovations with the spontaneous and incipient nature of the process, in a sector of vital importance for the economy and a valuable growth potential in line with the new dynamics and trends of the globalized world with highly demanding consumers in terms of health, well-being and improvement of quality of life and in a highly competitive environment (Traill and Meulenberg, 2002; Costa and Jongen, 2006; Trienekens and Zuurbier, 2008; Schiefer and Deiters, 2016). As a paradigm, open innovation is determined by the complex interaction of actors whose synergy projects the innovation system onto a given region. This context makes it essential to identify the main actors involved in the process and their form of interaction. By developing the proposed qualitative analysis exercise, the characteristics of the actors and their relationships in four production lines of the foodstuffs sector in Colombia (the meat sector, the dairy sector, the milling sector and the confectionery sector) are investigated. These sub-sectors were selected according to their degree of participation in domestic production. Through in-depth interviews, some companies in the Colombian food sector fall under the initial stage of open innovation. Additionally, the results suggest that companies acknowledge the importance of developing strategies with external actors, oriented according to public policy guidelines on innovation in Colombia.